2014
DOI: 10.1155/2014/328152
|View full text |Cite
|
Sign up to set email alerts
|

Large Dosage of Chishao in Formulae for Cholestatic Hepatitis: A Systematic Review and Meta‐Analysis

Abstract: Objective. To evaluate the efficacy and safety of large dosage of Chishao in formulae for treatment of cholestatic hepatitis. Methods. The major databases (PubMed, Embase, Cochrane Library, Chinese Biomedical Database Wanfang, VIP medicine information system, and China National Knowledge Infrastructure) were searched until January 2014. Randomized controlled trials (RCTs) of large dosage of Chishao in formulae that reported on publications in treatment of cholestatic hepatitis with total efficacy rate, togethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 27 publications
0
25
0
Order By: Relevance
“…Accumulating event suggests that free radicals are associated with apoptosis and lipid peroxidation in cholestatic lesions (Yang et al, 2009), and we believe that OS is a key factor for cholestatic damage (Ma et al, 2014). ANIT, a commonly used hepatotoxicant, can interrupt bile flow and accumulate bile acids in liver (Ohta et al, 1999).…”
Section: Discussionmentioning
confidence: 94%
“…Accumulating event suggests that free radicals are associated with apoptosis and lipid peroxidation in cholestatic lesions (Yang et al, 2009), and we believe that OS is a key factor for cholestatic damage (Ma et al, 2014). ANIT, a commonly used hepatotoxicant, can interrupt bile flow and accumulate bile acids in liver (Ohta et al, 1999).…”
Section: Discussionmentioning
confidence: 94%
“…Therefore, in this study, rats with ANIT treatment were applied to mimic the cholestasis and explore the potential mechanism of cholestatic hepatitis. Previous studies showed PLP exhibited multiple pharmacological effects, such as liver protection, anti‐oxidation, anti‐allergic, vasodilatation of thoracic aorta and immune‐regulation effects . Recent studies have highlighted that PLP exerts its pharmacological effects via anti‐inflammation effect .…”
Section: Discussionmentioning
confidence: 99%
“…In the United States, cholestasis is in the top 15 leading causes of death based on the statistics data from the Centers for Disease Control . In addition to these, cholestasis produces heavy patient and societal burdens in China . It is the condition that bile cannot flow from liver to duodenum, characterized by the reduction in bile flow and the excessive accumulation of bile acid as well as any other toxic compounds .…”
Section: Introductionmentioning
confidence: 99%
“…Paeoniflorin, a monoterpene glycoside, is one of the main bioactive components in Paeonia lactiflora Pall or Paeonia veitchii Lynch, which have been used for more than 2000 years in traditional Chinese medicine [16]. Paeoniflorin has been consistently shown to exhibit multiple pharmacological effects in liver disease [17].…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%